Magnetic-Fe/Fe3O4-nanoparticle-bound SN38 as carboxylesterase-cleavable prodrug for the delivery to tumors within monocytes/macrophages - Wang, Hongwang; Shrestha, Tej Bahadur; Basel, Matthew T.; Dani, Raj K.; Seo, Gwi-Moon; Balivada, Sivasai; Pyle, Marla M.; Prock, Heidy; Koper, Olga B.; Thapa, Prem S.; Moore, David; Li, Ping; et al. (My University, 2012)
The targeted delivery of therapeutics to the tumor site is highly desirable in cancer treatment, because it is capable of minimizing collateral damage. Herein, we report the synthesis of a nanoplatform, which is composed of a 15 ± 1 nm diameter core/shell Fe/Fe[subscript]3O[subscript]4 magnetic nanoparticles (MNPs) and the topoisomerase I blocker SN38 bound to the surface of the MNPs via a carboxylesterase cleavable linker. This nanoplatform demonstrated high heating ability (SAR = 522 ± 40 W/g) in an AC-magnetic field. For the purpose of targeted delivery, this nanoplatform was loaded into tumor-homing double-stable RAW264.7 cells (mouse monocyte/macrophage-like cells (Mo/Ma)), which have been engineered to express intracellular carboxylesterase (InCE) upon addition of doxycycline by a Tet-On Advanced system. The nanoplatform was taken up efficiently by these tumor-homing cells. They showed low toxicity even at high nanoplatform concentration. SN38 was released successfully by switching on the Tet-On Advanced system. We have demonstrated that this nanoplatform can be potentially used for thermochemotherapy. We will be able to achieve the following goals: (1) Specifically deliver the SN38 prodrug and magnetic nanoparticles to the cancer site as the payload of tumor-homing double-stable RAW264.7 cells; (2) Release of chemotherapeutic SN38 at the cancer site by means of the self-containing Tet-On Advanced system; (3) Provide localized magnetic hyperthermia to enhance the cancer treatment, both by killing cancer cells through magnetic heating and by activating the immune system.
Keywords: Cell-based delivery; Chemotherapeutic prodrug; Magnetic Fe/Fe3O4 nanoparticles; SN38